Enfrentando violência com a participação juvenil, uma avaliação do PRONASCI em Fortaleza - Cardoso, Lucileila de Sousa (2011)
This study aims to test the program called Programa Nacional de Segurança Pública com Cidadania (PRONASCI) in its axis “preventing the violence” with the constant youthful community involvement with the project named Projeto Proteção de Jovens em Território Vulnerável do Grande Bom Jardim, a neighborhood complex placed far from Fortaleza‟s downtown during the period between 2009/2010. It was sought an evaluation process in three parts: conception, implementation and results. This evaluation occurs from the understanding of the target population and technicians involved in PRONASCI / Protejo, and also from the critic analysis of the organizational and procedure problems and the projected goals. Among the relevant results of this evaluation it is possible to point the young people‟s ideas to fight the violence which can contribute to the best planning and performance of public politics that involves the youthful participation as an strategy to prevent and to control the violence